"Expect the Truth!" Exploiting History with Mandingo - DeVos, Andrew (American Studies, 2012)
The 1975 film Mandingo shocked audiences with its brutal and sexually-charged critique of the Hollywood plantation system canonized by Gone with the Wind. "Expect the Truth!" uses archival newspaper articles to tell the cultural history of Mandingo’s exhibition and reception, detailing the moral outrage of both white and black critics and the film’s acceptance by black audiences. These responses are then analyzed using Janet Staiger’s audience reception theory. The author concludes that the discourse surrounding Mandingo is best understood as a battle over the power to control both historical accounts of slavery and the cultural tastes of the viewing public.